Identification of Small-Molecule Inhibitors of Brucella Diaminopimelate Decarboxylase by Using a High-Throughput Screening Assay - Bie, Pengfei; Yang, Xiaowen; Zhang, Cunrui; Wu, Qingmin (Frontiers in Microbiology, 2020)
Brucellosis, caused by intracellular gram-negative pathogens of the genus Brucella, continues to be one of the most pandemic zoonotic diseases in most countries. At present, the therapeutic treatment of brucellosis relies on a combination of multiple antibiotics whichand involves a long course of treatment, leading to easy relapse, which may even lead to drug resistance in Brucella in some cases. and high side effects from the use of certain antibiotics (such as streptomycin). Thus, the need to identify novel drugs or targets to control this disease is urgent. Diaminopimelate decarboxylase (DAPDC), a key enzyme involved in the bacterial diaminopimelate (DAP) biosynthetic pathway, was suggested to be a promising anti-Brucella target in our previous study. In this work, the biological activity of Brucella melitensis DAPDC was characterized, and a library of 1591 compounds was screened for inhibitors of DAPDC. The results of a high-throughput screening (HTS) assay showed that twenty-four compounds inhibited DAPDC activity. In a further in vitro bacterial inhibition experiment, five compounds exhibited anti-Brucella activity (SID3, SID4, SID14, SID15 and SID20). These results suggested that the identified compounds can be used as potent molecules against brucellosis and that the application ranges of these approved drugs can be expanded in the future.